Chromatographic Separation and in Vitro Dissolution Assessment of Tenofovir disoproxil fumarate, Emtricitabine and Nevirapine in a Fixed Dose Combination of Antiretrovirals - Kalpana Jayapalu, Himaja Malipeddi, Anbarasu Chinnasamy (Journal of Applied Pharmaceutical Science, 2014)
A rapid, economic and robust stability indicating HPLC method was developed and validated to quantify Tenofovir disoproxil Fumarate (TDF), Emtricitabine (EMT) and Nevirapine (NVP) simultaneously at single wavelength (254 nm) in order to assess the in vitro drug release profile from tablet formulations. Chromatographic separation was performed with a gradient elution of samples on a 4.6 mm x 150 mm, 5 μm, Inertsil ODS-2 column with buffered mobile phase containing solvent A (10 Mm ammonium acetate buffer, pH 4.6) and solvent B ( acetonitrile) at a flow rate of 1.0 mL/min). In dissolution studies, the sink condition was optimized based on quantitative solubility of TDF, EMT and NVP standards in different dissolution medium as recommended by USP. The proposed HPLC method and dissolution test condition were validated as per ICH guidelines. The results obtained meet the regulatory criteria thereby confirming that the method is suitable for routine quality control analysis and in vitro dissolution studies.
Keywords: HPLC, Validation, Dissolution studies, Tenofovir disoproxil Fumarate, Emtricitabine, Nevirapine.